LIABILITY ON CORRUPTION CRIMINAL OFFENSES: INTERNATIONAL LEGAL ASPECT - Kulikov, Oleksii (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
The scientific article establishes the international regulatory and legal prerequisites for the formation of the national criminal law policy of Ukraine in the field of prevention and countermeasures against corruption criminal offenses. In the event of collisions, the problem of the correlation of international and national criminal legislation is identified. The formal-legal method and the method of interpretation (interpretation) were the methodological basis of the research. Exactly with the help of these methods it became possible to classify, systematize the studied international criminal law norms and to clarify the content of individual norms of criminal law. The author establishes that international legal acts do not contain an accurate and comprehensive definition of corruption and the terms that should be used when regulating corruption criminal offenses. These documents mainly include a list of corruption offenses that should be criminalized due to the increased degree of their social danger and are subject to criminalization. Anti-corruption measures are mainly reduced to the establishment of criminal liability for certain manifestations of corruption. The author notes that provisions of international legal acts should not be compilated completely. When improving the national criminal legislation, we have to take into account norms of the criminal legislation of Ukraine, which has been already established, instead. Currently, the borrowing of the experience of criminal law regulation in the field of anti-corruption contained in international legal acts, has a positive effect on the development of national anti-corruption legislation. The author notes that the signing of international treaties and the ratification of anti-corruption conventions contribute to the formation of relevant and effective legislation. The positive experience of such unification is one of the prerequisites for Ukraine’s accession to the European Union, and contributes to Ukraine’s active involvement in international anti-corruption cooperation.